IMPLEMENTASI PENAJAMAN PERAN DAN FUNGSI LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT MELALUI PEMETAAN PEMBERDAYAAN MODEL SYARAF KHAN - Sanusi, Anuar; Pulungan, M Sadat (Jurnal Manajemen Magister Darmajaya, 2015)
Research paradigm does not only look on the role and function LP2M in contribution to answer various problems of education in public and to recommend solution for decision maker in Kemendikbud. The strategic goal of PTS Darmajaya in 5 years (2012-2017) as analyzer unit in this research, are governance management that effective, efficient, transparent, accountable, and continue, and also management of education infrastructure. In order to reach those goals, LP2M arranges road map and master plan with various programs of research and community service for science development. LP2M serves to improve the quality of information services for students and faculty, and also in the search for alternative income by taking the advantage of the facilities and human resources in IBI Darmajaya. By support of human resources with a variety of different qualifications and skills, LP2M IBI Darmajaya take major task to synergize all of the powers into an integrated force and work as its functions.Keywords : empowerment, role, and function